تأثير فيروس موزاييك الخيار في إنتاجية صنفي التبغ بصما وبريليب في محافظة اللاّذقية - خدام, مازن; راعي, سليم; محمد, رامز (Latakia University Journal -Biological Sciences Series, 2019)
هدف البحث إلى دراسة تأثير الإعداء الميكانيكي بفيروس موزاييك الخيار في إنتاجية صنفي التبغ بصما وبريليب من الأوراق الخضراء والجافة وفي نسبة التصافي في محافظة اللاذقية. أظهرت النتائج اختلاف أعراض الإصابة وموعد ظهورها على الأوراق المعداة بالفيروس باختلاف الصنف, فظهرت على أوراق الصنف( بصما) بقعاً موضعية شاحبة تطوّرت مع تقدّم الإصابة إلى تماوت في عروق الأوراق ونسيجها مع الانتشار ألجهازي لأعراض الموزاييك. أمّا على الصنف (بريليب) فظهرت أعراض الموزاييك الأخضر. وأدت الإصابة بالفيروس إلى تقزّم النباتات المصابة بنسبة 19.96% و 12.19% في الصنف ( بصما ) بعد 45 و 87 يوماً بعد الإعداء بالفيروس على التوالي, وبنسبة 24.74% و 20.37% على التوالي في نباتات الصنف (بريليب). كما أدّت الإصابة إلى خفض في إنتاجية الصنف (بصما) من الأوراق الخضراء ومن الأوراق الجافة بنسبة 20%, وكانت نسبة التصافي 102%, في حين كان الفقد في إنتاجية الصنف (بريليب) 29% و 26% على التوالي وكانت نسبة التصافي 112%. This research aims at studying the effect of mechanical inoculation with Cucumber Mosaic cucumovirus (CMV) on the productivity of tobacco varieties (Basma and Prilep) in Lattakia Governorate. The results show variation in infection symptoms and their time of appearance among varieties at issue; inoculated leaves of Basma show chlorotic local lesions developed as a consequence of vein and tissue necrosis accompanied by systematic mosaic, where green mosaic is observed on the leaves of inoculated Brilep plants. The CMV infection has caused stunting in inoculated Basma plants 19.96% and 12.19% after 45 days and 87 days of post- inoculation, respectively, and the stunting rates for Prilep plants are 24.74% and 20.37%, respectively. The viral infection with CMV has decreased the production of Basma crop of fresh and dry leaves by 20%. The gross net ratio is 102%, whereas the losses in productivity for Prilep crop are 29% and 26%, respectively, with the gross net ratio being 112%.